2012
DOI: 10.1002/ejic.201200613
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Palladium‐Catalysed Direct Arylation Followed by Suzuki Coupling of Bromo‐2‐chloropyridines: Simple Access to a Variety of 2‐Arylpyridines

Abstract: Abstract2‐Arylpyridines are an important class of ligands for the synthesis of complexes with physical properties. We observed that the use of 3‐, 4‐ or 5‐bromo‐2‐chloropyridines allows the synthesis of a wide variety of heteroarylated 2‐arylpyridines by means of successive direct arylation and Suzuki coupling. For these two reactions, an air‐stable catalyst associated to a cheap and nontoxic base was employed as the catalyst. Moreover, a wide range of heteroarenes and functionalised arylboronic acids could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Doucet and co-workers also investigated the PdA C H T U N G T R E N N U N G (OAc) 2 /dppb-catalyzed arylation of 2-substituted furans with equimolar amounts of commercially available bromo-2-chloropyridines and found that 5-aryl derivatives of general formula 58 were obtained in good yields using, also in this case, KOAc as the base and DMA as the solvent (Scheme 22). [32] A quite low yield was, however, obtained in the PdA C H T U N G T R E N N U N G (OAc) 2 /dppb-catalyzed C-3 arylation of 2-ethylbenzo[b]furan (59) with 4-bromo-2-chloropyridine (Scheme 23). [32] It was then observed that the heteroarylated 2-chloropyridines resulting from the chemoselective C-5 arylation of 2-substituted five-membered heteroarenes bearing one or two heteroatoms with 4-bromo-2-chloropyridine were able to undergo PdA C H T U N G T R E N N U N G (OAc) 2 /dppbcatalyzed Suzuki-type reactions with arylboronic acids to give 2-arylpyridine derivatives in high yields.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
See 3 more Smart Citations
“…Doucet and co-workers also investigated the PdA C H T U N G T R E N N U N G (OAc) 2 /dppb-catalyzed arylation of 2-substituted furans with equimolar amounts of commercially available bromo-2-chloropyridines and found that 5-aryl derivatives of general formula 58 were obtained in good yields using, also in this case, KOAc as the base and DMA as the solvent (Scheme 22). [32] A quite low yield was, however, obtained in the PdA C H T U N G T R E N N U N G (OAc) 2 /dppb-catalyzed C-3 arylation of 2-ethylbenzo[b]furan (59) with 4-bromo-2-chloropyridine (Scheme 23). [32] It was then observed that the heteroarylated 2-chloropyridines resulting from the chemoselective C-5 arylation of 2-substituted five-membered heteroarenes bearing one or two heteroatoms with 4-bromo-2-chloropyridine were able to undergo PdA C H T U N G T R E N N U N G (OAc) 2 /dppbcatalyzed Suzuki-type reactions with arylboronic acids to give 2-arylpyridine derivatives in high yields.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
“…[32] A quite low yield was, however, obtained in the PdA C H T U N G T R E N N U N G (OAc) 2 /dppb-catalyzed C-3 arylation of 2-ethylbenzo[b]furan (59) with 4-bromo-2-chloropyridine (Scheme 23). [32] It was then observed that the heteroarylated 2-chloropyridines resulting from the chemoselective C-5 arylation of 2-substituted five-membered heteroarenes bearing one or two heteroatoms with 4-bromo-2-chloropyridine were able to undergo PdA C H T U N G T R E N N U N G (OAc) 2 /dppbcatalyzed Suzuki-type reactions with arylboronic acids to give 2-arylpyridine derivatives in high yields. [32] The synthesis of 1-[5-(2-phenylpyridin-3-yl)furan-2-yl]-butan-1-one (60) from compound 58d and phenylboronic acid is illustrated in Scheme 24.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
See 2 more Smart Citations
“…Doucet and co‐workers also investigated the Pd(OAc) 2 /dppb‐catalyzed arylation of 2‐substituted furans with equimolar amounts of commercially available bromo‐2‐chloropyridines and found that 5‐aryl derivatives of general formula 58 were obtained in good yields using, also in this case, KOAc as the base and DMA as the solvent (Scheme ) 32…”
Section: Intermolecular Direct (Hetero)arylation Of Five‐membered Hmentioning
confidence: 99%